Amina Wadud's Gender Hermeneutics on QS. An-Nisa: 34: Criticism of Patriarchal Bias and Its Relevance to Contemporary Women's Thought - Cahya, Hafiza Afari; Bukhari, Rauuf; Yumna, Hayatul; Milhan, Rumaisha; Akbar, Abil; Nurrohim, Ahmad (Journal of English Language and Education, 2025)
This study examines Amina Wawud's interpretation of QS. An-Nisa: 34 through a feminist interpretive approach in response to gender bias in classical interpretations that tend to be patriarchal. The focus of this study is how the dominance of traditional interpretations gives legitimacy to the superiority of men over women in the domestic realm. The purpose of this research is to explore the hermeneutic offer of Wadud that is more oriented towards gender justice and equality. The research uses a qualitative method based on literature studies with primary sources in the form of Amina Wadud's work Qur'an and Woman. The results of the study show that Wadud interprets the word qanitāt as "good woman" and not just "obedience to the husband"; nusyūz is understood as domestic disharmony, not just the disobedience of the wife; and ḍaraba is not interpreted as "hitting", but rather emphasizing non-violent settlement. In conclusion, Wadud's feminist interpretation opens up a space for a more gender-fair reading of the Qur'an, as well as makes a significant contribution to strengthening the Muslim feminist movement in fighting for the equal role of women in the domestic and public spheres. The contribution of this research lies in the effort to deconstruct patriarchal interpretations and their relevance to the discourse of gender equality in contemporary social contexts.